Additive Manufacturing, Modeling and Performance Evaluation of 3D Printed Fins for Surfboards. (31st January 2017) - Gately, Reece D.; Beirne, Stephen; Latimer, Geoff; Shirlaw, Matthew; Kosasih, Buyung; Warren, Andrew; Steele, Julie R.; in het Panhuis, Marc
ABSTRACT: We demonstrate that Additive Manufacturing (3D printing) is a viable approach to rapidly prototype personalised fins for surfboards. Surfing is an iconic sport that is extremely popular in coastal regions around the world. We use computer aided design and 3D printing of a wide range of composite materials to print fins for surfboards, e.g. ABS, carbon fibre, fibre glass and amorphous thermoplastic poly(etherimide) resins. The mechanical characteristics of our 3D printed fins were found to be comparable to commercial fins. Computational fluid dynamics was employed to calculate longitudinal (drag) and tangential (turning) forces, which are important for surfboard maneuverability, stability and speed. A commercial tracking system was used to evaluate the performance of 3D printed fins under real-world conditions (i.e. surfing waves). These data showed that the surfing performance of surfboards with 3D printed fins is similar to that of surfboards with commercial fins.